Nigerian propolis: chemical composition, antioxidant activity and α-amylase and α-glucosidase inhibition. Issue 18 (17th September 2021) - Alaribe, Chinwendum Stephenie; Esposito, Tiziana; Sansone, Francesca; Sunday, Adesegun; Pagano, Imma; Piccinelli, Anna Lisa; Celano, Rita; Cuesta Rubio, Osmany; Coker, Herbert Alexander; Nabavi, Seyed Mohammad; Rastrelli, Luca; Picerno, Patrizia
Abstract: Propolis is an attractive natural ingredient to design health products due to its pharmacological effects. Our chemical investigation of a polar extract of Nigerian propolis (NP) led the isolation and identification of five isoflavonoids (1-4, 6 ), one diarylpropane (5 ) and one prenylated flavanone (7 ) by the combination of chromatographic and spectroscopic techniques. Compounds 1, 4 and 7 were found to be the main markers in NP (8.0, 5.0 and 4.0 mg/g of dry extract, respectively). Moreover, NP and its phenolic constituents exhibited in vitro free radical scavenging activity together with a promising antidiabetic effect against α-amylase and α-glucosidase enzymes. Finally, NP showed also a moderate inhibition of Helicobacter pylori growth. These results suggested that NP could be a good candidate in nutraceuticals and food products. Abstract : UF0001